Bravo! : Poems About Amazing Hispanics - Engle, Margarita; Lopez, Rafael 1961- (New York : Henry Holt and Company, 2017)
"Bold, graphic portraits and beautiful poems present famous and lesser-known Latinos from varied backgrounds who have faced life's challenges in creative ways."--Provided by publisher.
Keywords: Latin Americans -- Biography; Hispanic Americans -- Biography; Latin Americans; Hispanic Americans